1991
DOI: 10.1097/00006123-199105000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Conservative treatment of patients with acoustic tumors

Abstract: Seventy of 178 patients with acoustic tumors initially were treated conservatively and have been followed up for an average of 26 +/- 2 months. The tumor size was determined by the mean maximum anteroposterior and mediolateral diameters, using computed tomographic or magnetic resonance imaging scans obtained sequentially throughout the follow-up period. The average tumor growth was 1.6 +/- 0.4 mm the 1st year, and 1.9 +/- 1.0 mm the 2nd year (range, -2 to 17 mm/y): 4 tumors showed apparent regression, 28 (40%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
81
3

Year Published

1993
1993
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(92 citation statements)
references
References 0 publications
8
81
3
Order By: Relevance
“…Tschudi et al [13] found that patients with progressive hearing loss as a Wrst symptom had a signiWcantly lower tumor growth than those presenting with tinnitus, sudden hearing loss and vertigo. Other studies, however, revealed no signiWcant diVerences in age, gender, tumor laterality, initial symptoms, duration of symptoms or initial tumor size between patients with growing tumors and non-growing tumors [7,11,12,14]. A possible predictor of growth may be the duration of symptoms.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Tschudi et al [13] found that patients with progressive hearing loss as a Wrst symptom had a signiWcantly lower tumor growth than those presenting with tinnitus, sudden hearing loss and vertigo. Other studies, however, revealed no signiWcant diVerences in age, gender, tumor laterality, initial symptoms, duration of symptoms or initial tumor size between patients with growing tumors and non-growing tumors [7,11,12,14]. A possible predictor of growth may be the duration of symptoms.…”
Section: Discussionmentioning
confidence: 94%
“…Fucci et al [11] reported a signiWcantly increased growth rate of tumors with a maximal diameter larger than 20 mm at presentation. Some studies found that tumor growth in the Wrst year could be indicative for future growth [12,13]. Furthermore the symptoms of the patients have been considered as possible predictors of growth.…”
Section: Discussionmentioning
confidence: 99%
“…The natural history of VSs is not well known; retrospective studies suggest that 53% continuously grow and 7% to 10% remain stable, whereas up to 30% involute (16). A few prospective series showed that untreated VSs regress in 7% to 20% of cases and remain stable in 40% to 85% (2, 1721) whereas only 18% to 55% tumors show progression (2, 1719, 21).…”
Section: Discussionmentioning
confidence: 99%
“…The traditional method of assessing tumour size is a single (axial) linear measurement. [5][6][7][8][9][10][11][12][13] This approach is relatively simple, quick and does not require a computer workstation but has disadvantages. First, the choice of which axial measurement to make is not straightforward.…”
Section: Methods Of Measuring Tumour Sizementioning
confidence: 99%